In ovulo rescue of hybrid embryos in flame seedless grapes - influence of pre-bloom sprays of benzyladenine - Bharathy, P. V.; Karibasappa, G. S.; Patil, S. G.; Agrawal, Dinesh C. (Scientia Horticulturae, 2005)
Based on the theory that cytokinins are known to increase the sink strength of seeds for assimilates, the present investigation was carried out to study the influence of pre-bloom and bloom time sprays of benzyladenine (BA) on embryo recovery, germination and plant development in Flame Seedless grape variety by using in ovulo rescue methods. The combined effect of pollen parent type and sprays of BA drastically improved these parameters and the embryo recovery was more than doubled in all the crosses, except in cross FS x Concord. Also, germination of embryos was higher when BA sprays were given. Recovery of embryos and growth depended on BA treatment and the pollen parent types. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: benzyladenine; flame seedless; in ovulo embryo rescue; interspecific hybridization; Vitis spp.